2022
DOI: 10.7759/cureus.21294
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Retrospective Analysis on the Etiology of Bradycardia in COVID-19 Patients

Abstract: IntroductionBradycardia has been reported in the setting of SARS-CoV2 (COVID-19) and appears to be an important cardiac manifestation with an association of mortality. However, the etiology of bradycardia in COVID-19 remains unclear. Therefore, this study aims to retrospectively investigate the potential causes of bradycardia in COVID-19 patients. MethodThe multicenter retrospective analysis consisted of 1,116 COVID-19 positive patients from March 2020 to March 2021. Bradycardia and severe bradycardia were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
0
17
2
Order By: Relevance
“…At difference with another study [ 13 ], where no correlation was found between RDV administration and bradycardia, in our analysis the occurrence of bradycardia was statistically greater in RDV-treated patients compared to the CTR group. This observation suggests a possible causal association between RDV administration and the occurrence of bradycardia, which could not be totally explained by SARS-CoV-2 infection or hospital stay.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…At difference with another study [ 13 ], where no correlation was found between RDV administration and bradycardia, in our analysis the occurrence of bradycardia was statistically greater in RDV-treated patients compared to the CTR group. This observation suggests a possible causal association between RDV administration and the occurrence of bradycardia, which could not be totally explained by SARS-CoV-2 infection or hospital stay.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation suggests a possible causal association between RDV administration and the occurrence of bradycardia, which could not be totally explained by SARS-CoV-2 infection or hospital stay. The discrepancy with our finding could be due to the different patient selection criteria since the study by Umeh et al [13] was not specifically focused on RDV treatment, but on all the causes of bradycardia in COVID-19 patients, therefore patients treated with RDV and control patients were not matched. Our results are instead in agreement with two previous case-control studies [11,12], which reported an increased incidence of bradycardia in the group of patients treated with RDV although with different percentages probably due to the different HR monitoring methods: Attena et al [11] considered the HR at the day of the hospitalization and at day fifth of RDV therapy, while Pallotto et al [12] considered the days of RDV treatment, as we did, however, without considering the following five day.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…showed that the incidence of bradycardia was associated with length of hospital stay (OR: 1.071, 95% CI: 1.049-1.094), mortality (OR: 1.600, 95% CI: 1.070-2.394), ventilator use (OR: 0.470, 95% CI: 0.298-0.742), and steroid use (OR: 0.559, 95% CI: 0.402-0.776), whereas remdesivir treatment did not reveal any signi cant difference [23]. Consistent with our results, the multivariate analysis of Umeh et al's study revealed that remdesivir treatment was not associated with bradycardia, suggesting that the hypothesis on the association between remdesivir treatment and bradycardia may have been affected by other confounding factors.…”
Section: Discussionmentioning
confidence: 89%
“…Compared to placebo, a number of randomized controlled trials have observed a reduction in LOS and increased hospital discharge rates in patients receiving remdesivir [ 14 , 50 , 51 ]. However, this potential benefit has been challenged in follow-up studies [ 52 55 ] under the pretense that completing the full therapeutic course may be taking precedence over earlier discharges in otherwise recovering patients [ 56 59 ]. In relation to bradycardia, one study observed extended hospital stays in COVID-19 patients with bradycardia [ 58 ], while another found similar LOS between RAB and non-RAB patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%